Proses Interaksi Sosial Masyarakat Pedesaan Dalam Kajian Perspektif Sosiologi Hukum - Lily, Lily Yusni Aprilianti; Ukas (LPPM Universitas Putera Batam, 2024)
Social interaction is the key to all social life because without social interaction, there can beno shared life. Social interaction is very important in people's lives because socialinteraction will occur when individuals with individuals and groups with human groups whotalk to each other, cooperate, and so on to achieve a common goal, hold competitions,disputes even social control, and so on. Therefore, it can be said that social interaction isthe basis of the social process, which refers to dynamic relationships. The requirements ofsocial interaction are, the absence of social contact and the absence of communication.Meanwhile, society in a broad sense is a group of people who are closely intertwinedbecause of certain systems, certain traditions, conventions and laws alike, and lead tocollective life. According to Soerjono Soekanto, the characteristics of society are living ingroups, giving birth to culture, changing, interaction, the absence of leaders, and havingsocial stratification. The community was also divided into several factions that were the firstto be family, then developed into a community of people, then increased into a politicalsociety, and led to the establishment of formal institutions of the State. In addition, the ruralcommunity is a society that generally still holds cultural values and also still holds thehereditary customs of the ancestors. A common characteristic of rural communities is thatvillagers always have special characteristics in community life including in the running ofsocial interaction. As for the characteristics, namely, working together in doing something,facilities that are still very limited and simple, have a kinship that is still very close, and soon. However, in certain situations and conditions, some characteristics of ruralcommunities undergo several changes including how to interact due to the development oftechnology and information that developed in the era of globalization and the era ofmodernization. Sociology wich means the science that studies society or the dynamics ofsociety or the legal social institutions governing society.